Orthodoxie fédéraliste et relations régionales transfrontières, une menace illusoire - Bissonnette, Lise (Études internationales, 1981)
Following a few studies published in the United States and Canada, the author examines formal relations between some American states and Canadian provinces to assess their effect on the conduct of relations between both federal governments. She studies the regional "summits" where American governors meet Canadian premiers, particularly the annual Conference of New England Governors and Quebec and Maritime premiers, with some references to similar organizations just beginning in the West, and in the South with Mexican states. She concludes that federal governments keep substantial control over this "regional diplomacy". Washington and Mexico retain control more directly, and Canada indirectly via major subsidies to some provincial programs, and rulings on international economic relations. As a political instance, the regional Conference has gone from a goal of « integrated regional development » in 1974, to a simple « agency for mutual information » today. Its decisions do not seem to contradict federal policies in any significant way. In Canada, it may nevertheless induce a vague for m of continentalism, going contrary to Ottawa's new nationalism.